Nested polymerase chain reaction for early diagnosis of typhoid fever - Sultana, S; Hossain, MA; Alam, MA; Paul, SK; Mahmud, C; Kabir, MR; Haque, N; Yasmin, T; Kayes, MT; Maruf, AA; Kobayashi, N (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):21-27 The abstract of this article is available on the PubMed website